The Evolution of the Sustainability Assessment Tool SBToolPT: From Buildings to the Built Environment. (1st January 2014) - Castanheira, Guilherme; Bragança, Luís
Abstract : This paper analyses the current trends in sustainability assessment. After about 15 years from the launch of sustainability assessment tools, focused on buildings evaluation, the paradigm of sustainability assessment tools is changing from the building scale to the built environment scale. Currently European cities and cities around the world are concerned with sustainable development, as well as its evolution. Cities seek a way to adapt to contemporary changes, in order to meet the required needs and ensure population's well-being. Considering this, the new generations of sustainability assessment tools are being developed to be used to guide and help cities and urban areas to become more sustainable. Following the trend of the most important sustainability assessment tools, the sustainability assessment tool SBTool PT is also developing its version for assessing the sustainability of the built environment, namely, the urban planning projects and the urban regeneration projects, to be developed in Portugal, the SBTool PT -UP. The application of the methodology to three case studies will demonstrate its feasibility; at the same time this will identify the best practices which will serve as reference for new projects, thereby assisting the development of the tool.